Combined transcriptome and metabolome analysis of the resistance mechanism of quinoa seedlings to Spodoptera exigua - Liu, Junna; Li, Li; Liu, Yongjiang; Kong, Zhiyou; Zhang, Ping; Wang, Qianchao; Cheng, Shunhe; Qin, Peng (Frontiers in Plant Science, 2022)
Abstract: Quinoa has attracted considerable attention owing to its unique nutritional, economic, and medicinal values. The damage intensity of Spodoptera exigua at the seedling stage of quinoa fluctuates with the crop's biological cycle and the environmental changes throughout the growing season. In this study, we used independently selected quinoa seedling resistant and susceptible cultivars to investigate the difference between insect resistance and insect susceptibility of quinoa at the seedling stage. Samples were collected when Spodoptera exigua 45 days after planting the seedlings, and broad targeted metabolomics studies were conducted using liquid chromatography-mass spectrophotometry combined with transcriptomic co-analysis. The metabolomic and genomic analyses of the insect-resistant and insect-susceptible quinoa groups revealed a total of 159 differential metabolites and were functionally annotated to 2334 differential genes involved in 128 pathways using the Kyoto Encyclopedia of Genes and Genomes analysis. In total, 14 metabolites and 22 genes were identified as key factors for the differential accumulation of insect-resistant metabolites in quinoa seedlings. Among them, gene-LOC110694254, gene-LOC110682669, and gene-LOC110732988 were positively correlated with choline. The expression of gene-LOC110729518 and gene-LOC110723164, which were notably higher in the resistant cultivars than in the susceptible cultivars, and the contents of the corresponding metabolites were also significantly higher in the resistant cultivars. These results elucidate the regulatory mechanism between insect resistance genes and metabolite accumulation in quinoa seedlings, and can provide a basis for the breeding and identification of new insect-resistant quinoa cultivars as well as for screening potential regulatory metabolites of quinoa insect-resistant target genes.